Cabaran majalah Pengasuh sebagai medium dakwah - Yazilmiwati Yaacob, * (Sunway University College, 2004)
This paper presents research findings on the challenges faced by the magazine Pengasuh as a medium to propagate Islamic knowledge. Although this magazine has been in circulation for almost a century now, its effort to disseminate Islamic teachings has not been very successful when compared to some other similar publications in Malaysia. The study used two types of research methods: library research and field research. The library research was used to collect information on the history of Pengasuh and the role of the publishing media in propagating religious knowledge. The fieldwork method involved interviewing those directly involved with the publication of Pengasuh. The results of the study show that in terms of content, the coverage of Pengasuh has been both substantive and relevant to the propagation of Islamic knowledge. However, there exist a number of weaknesses in the planning and management of the magazine which appear to have contributed to the poor circulation of the magazine. The paper ends with suggestions on how to improve the production and circulation of the magazine so that it can play a more effective role in the propagation of Islamic teaching.